A phenomenological study of EFL teachers’ experiences in teaching critical reading - Ikaningrum, Rini Estiyowati; Suryaman, Maman; Triastuti, Anita (International Journal of Innovative Research and Scientific Studies, 2025)
Critical reading plays a crucial role in developing students’ critical literacy, enabling them to engage deeply with knowledge and apply it throughout their lifelong learning journey. However, there remains a lack of research exploring how teachers design and implement strategies to balance passive and active critical reading activities, particularly in EFL (English as a Foreign Language) classrooms in Indonesian higher education. This study seeks to fill this gap by examining the strategies used by English teachers to cultivate critical reading skills in university students. Using a phenomenological study, data were collected through structured interviews with six English teachers from four universities in Indonesia. The data were analyzed using Atlas.ti8, revealing two primary categories of critical reading strategies: passive and active. Passive strategies include guiding students to answer questions with diverse arguments, critique reading content, comprehend reading passages, and consult dictionaries for unfamiliar words. In contrast, active strategies involve previewing information, reading passages in detail, interpreting visual elements such as charts and diagrams, summarizing content, taking notes, and participating in discussions and reviews. This study highlights the importance of a balanced approach to critical reading, providing a practical framework for integrating passive and active strategies in EFL classrooms. By doing so, it offers valuable insights for English teachers seeking to enhance their students’ critical literacy and adapt their teaching practices to meet the demands of a globalized educational landscape. This research not only addresses a critical gap in the field but also contributes to the broader discourse on effective EFL pedagogy.